Systematic synthesis of community-based rehabilitation (CBR) project evaluation reports for evidence-based policy: a proof-of-concept study - Wirz Sheila; Kuipers Pim; Hartley Sally (BMC, 2008)
Abstract Background This paper presents the methodology and findings from a proof-of-concept study undertaken to explore the viability of conducting a systematic, largely qualitative synthesis of evaluation reports emanating from Community Based Rehabilitation (CBR) projects in developing countries. Methods Computer assisted thematic qualitative analysis was conducted on recommendation sections from 37 evaluation reports, arising from 36 disability and development projects in 22 countries. Quantitative overviews and qualitative summaries of the data were developed. Results The methodology was found to be feasible and productive. Fifty-one themes were identified and the most important ones of these are presented to illustrate the significance of the method. The relative priorities of these themes indicated that "management" issues were the primary areas in which recommendations were made. Further analysis of themes reflected the emphasis evaluators placed on the need for enhanced management, organisational, personnel and administrative infrastructure in CBR projects. Evaluators consistently recommended that CBR projects should be more connected and collaborative at governmental, organisational, political and community levels. The synthesis also noted that evaluators questioned the emphasis in CBR on project expansion and income generation. Conclusion The application of the synthesis methodology utilised in this proof-of-concept study was found to be potentially very beneficial for future research in CBR, and indeed in any area within health services or international development in which evaluation reports rather than formal "research evidence" is the primary source material. The proof-of-concept study identified a number of limitations which are outlined. Based on the conclusions of 37 evaluation reports, future policy frameworks and implementation strategies in CBR should include a stronger emphasis on technical, organisational, administrative and personnel aspects of management and strategic leadership.